THE COMIC AS A MEDIUM OF LEARNING IN READING JAVANESE SCRIPT OF THE 7TH GRADE STUDENTS OF JUNIOR HIGH SCHOOL - sup, Suprihati (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2018)
ABSTRACT This study aims to (1) describe the characteristics of students and teachers necessary to read java script using media, (2) to formulate the prototype of Javanese script comic media, and (3) to present the professional result to the Javanese script comics for the seventh grade students of Junior High School. This research use Research and Development (R & D)’s approach. Data collected by observation, interviews, and questionnaires. The result of the research is the creation of comic’s product as learning’s media of reading Javanesse script in 7th grade students of Junior High School. Dialogue text writing and narrative text in comics, using Javanese script. This comic’s media choose the folklore of Mrapen as a story in comics. Learning media such as Javanesse scricpt’s comic receive an agreement by the professional of material and media. that assesment agreethe media of Jaavanesse script comic has been qualified and could be usesuch as media in Javanesse language, in particular of Javanesse script in 7th grade Junior High Student. Keywords: comic, media, Java script, Junior High School.